SEASONAL FISHING PATTERN OF MATURE NARROW-BARRED SPANISH MACKEREL (SCOMBEROMORUS COMMERSON) IN KEPULAUAN RIAU PROVINCE WATERS - Fardilah, Muhammad Fajar Fajri; Sari, Tengku Ersti Yulika; Simbolon, Domu; Sondita, Muhammad Fedi Alfiadi; Putra, Demo Buana (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Narrow-barred Spanish mackerel (Scomberomorus commerson) is one of the high-value commercial fish species exported from the Riau Archipelago. To meet export standards, this species must fulfill specific quality criteria to be considered suitable for export. This study aims to analyze the fishing season pattern and size structure of catchable Spanish mackerel (Scomberomorus commerson) in the waters of the Riau Archipelago. Data were collected through field surveys, direct observation of catches, and analysis of gillnet vessel logbook records from 2018 to 2022. Fishing productivity was calculated using catch per unit effort (CPUE), and the seasonal pattern was identified using the Simple Moving Average (SMA) method and monthly fishing season index (Mt,b). The results showed that the fishing season for Spanish mackerel occurs from January to May, with the peak season in February. The size structure analysis revealed that 87.6% of the sampled fish were larger than 61 cm, indicating that they had reached first maturity (catchable size). Nevertheless, a portion of smaller fish was still caught, highlighting the need for improved management of fishing gear and fishing grounds to support resource sustainability. These findings, once implemented, are expected to significantly improve the sustainability of Spanish mackerel populations, offering hope for the future of this species. These findings are expected to contribute to the implementation of precision fisheries management in Fisheries Management Area (FMA) 711. Key words: catchable size, catch per uni effort, fishing season pattern, precision fisheries, Spanish mackerel